Exploring Trends in Labor Informality in Latin America, 1990-2010 - Leopoldo Tornarolli; Diego Battistón; Leonardo Gasparini; Pablo Gluzmann (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
Labor informality is a pervasive characteristic of the labor markets in Latin America, and a central issue in the public policy debate. This paper discusses the concept of labor informality and implements alternative definitions using microdata from around 300 national household surveys in all Latin American countries. The analysis covers two decades: while labor informality, defined as lack of social protection related to employment, remained with few changes in the 1990s, there is a discernible downward pattern during the 2000s in most countries. These movements reveal a counter-cyclical behavior of labor informality, that may be linked to segmentation in the labor market.
Keywords: 330; labor informality; employment; Latin America; labor market